Estimation of Weibull distribution parameters to assess the wind energy potential of high altitude sites in the Andean region of Ecuador - Natalia Alexandra Pérez Londo; Darwin Saúl Lema Londo; Rosa Ormaza Hugo; Fabián Londo; Narcisa Sánchez Salcán; Diana Katherine Campoverde-Santos; Dalinda Quingatuña; Julio Coello-Cabezas (Results in Engineering, 2025)
The Andean region of Ecuador has considerable untapped wind potential, especially at high altitudes where wind characteristics such as speed and constancy are more favorable. In this context, the objective of this study is to use eight numerical methods to estimate the shape and scale parameters of the Weibull distribution to determine the wind potential at two sites in the Andean region, located above 4300 m ASL. It also aims to determine whether similar altitudes in relatively close locations offer similar conditions for wind energy production. It also shows how wind power density changes over time. Wind speed data from a three-year period (2018–2020) were analyzed. The methods applied are maximum likelihood, the method of moments, the power density method, the empirical Lysen method, the empirical Justus method, the energy pattern factor method, the alternative maximum likelihood method, and the standard deviation method. To evaluate the accuracy of these methods, the mean square error, the root mean square error, the mean absolute error, the coefficient of determination, and the chi-square test were used. The results of the statistical analysis indicate that the empirical Lysen method and the maximum likelihood method were the most accurate in determining the Weibull parameters at the study sites. With a most probable velocity of 8.28 m/s and a power density categorized as excellent, a wind power generation project could be developed at the Pinanquil site. Furthermore, it is emphasized that the most accurate method is not analogous across sites due to differences in wind characteristics.